Yield line analysis of two way reinforced concrete slabs having two adjacent edges discontinuous with opening - Part II : Design tables and application - Kumar, Veerendra; Bandyopadhyay, Milan (Journal of Structural Engineering, 2025)
The yield line analysis of reinforced concrete rectangular slabs having adjacent edges discontinuous with opening had been carried out in Part I of this paper. The ratios of the corresponding lengths of the sides of the opening and the slab are kept the same and the size of opening up to half the length of the slab sides are considered. The ratio of the span moments to support moments is kept 0.75. The design tables and the example to explain the use of the tables for analysis of slab are also presented in this paper.